Divergent responsiveness of two isoforms of the estrogen receptor to mixtures of contaminants of emerging concern in four vertebrates. Issue 5 (26th December 2017) - Kohno, Satomi; Katsu, Yoshinao; Cipoletti, Nicholas; Wang, Lina C.; Jorgenson, Zachary G.; Miyagawa, Shinichi; Schoenfuss, Heiko L.
Abstract: Contaminants of emerging concern (CECs) are ubiquitous in aquatic environments with well‐established endocrine‐disrupting effects. A data matrix of 559 water samples was queried to identify two commonly occurring CECs mixtures in Great Lakes tributaries. One mixture consisted of eight agricultural CECs (AG), while another contained 11 urban CECs (UB). The known estrogenic compounds bisphenol A, estrone and nonylphenol were present in both mixtures. According to the EPA Tox21 in ToxCast database, AG and UB mixture at an environmentally relevant concentration were estimated to account for 6.5% and 3.4% estrogenicity of the model endocrine disruptor estradiol‐17β, respectively. Two isoforms of the estrogen receptor (Esr1 and ‐2, former Erα and Erβ) cloned from fathead minnow, bluegill sunfish, American alligator and human, responded differently to AG and UB mixtures. Human and bluegill Esr1 were the most sensitive to AG and UB mixtures, respectively. Fathead minnow Esr1 and Esr2b were the least sensitive to 10× AG and UB in estrogen dose equivalents, respectively. Even at environmentally documented concentrations, UB significantly activated bluegill Esr1. Moreover, 100× concentrated UB hyperstimulated fathead minnow Esr1 beyond the maximum induction of estradiol‐17β. These results indicate that efficacious receptors and species differ in their response to CEC mixtures. Furthermore, estrogenicity may be present in some CECs not previously considered estrogenic, or, alternatively, estrogenicity of a mixture may be enhanced through chemical interactions. Our study highlights the need for further studies of CECs utilizing a variety of receptors cloned from diverse species. Abstract : Two commonly occurring contaminants of emerging concern (CECs) mixtures in Great Lakes tributaries, agricultural and urban CECs, differently stimulated two isoforms of the estrogen receptor cloned from fathead minnow, bluegill, American alligator and human in an in vitro transactivation assays. Concentrated urban CEC mixtures hyperstimulated fathead minnow estrogen receptor 1 beyond the maximum induction of estradiol‐17β. Our study highlights the need for further studies of CECs utilizing a variety of receptors in diverse species.